The Influence Of Benevolen Leadership And Organizational Culture On Innovation Capability At Dewi Sartika General Hospital Kendari - Alfina Fatresia Wulandari; Niar Astaginy; Ismanto Ismanto (Global Leadership Organizational Research in Management, 2023)
This study aims to determine (1) the influnce of Benevolen Leadership on Innovation Capability at Dewi Sartika Kendari General Hospital. (2) the influence of Organizational Culture on Innovation Capability. This researh uses a quantitative method approach. Data collection in this research used study interviews, literature study, and distributing questionnaires. The population of this study were all nurses at Dewi Sartika Kendari General Hospital, while the sample of this study was 90 people. The research instruments using validity and reliability testswith SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and the structural model testing (inner model) with Smart PLS 3.0. Based on the research results, it is known that there is a positive and significant influence between the Benevolen Leadership variable on Innovation Capability as shown by the average value of 3.426 with a P- Volne of 0.001. Meanwhile, the organizational culture variable has a positive and significant effect on innovation capability as indicated by a tattoo value of 2.254 with a P valueof 0.025.